A systemic approach to the quantification of the phenotypic plasticity of plant physiological traits: the multivariate plasticity index. (19th November 2020) - Pennacchi, João Paulo; Lira, Jean Marcel Sousa; Rodrigues, Marcelo; Garcia, Fernando Henrique Silva; Mendonça, Ane Marcela das Chagas; Barbosa, João Paulo Rodrigues Alves Delfino
Abstract : The multivariate plasticity index allows the evaluation in a systemic way of phenotypic plasticity of multiple traits in plant ecophysiology experimentation, integrating characteristics at multiple plant levels. Abstract: The phenotype of an individual emerges from the interaction of its genotype with the environment in which it is located. Phenotypic plasticity (PP) is the ability of a specific genotype to present multiple phenotypes in response to the environment. Past and current methods for quantification of PP present limitations, mainly in what constitutes a systemic analysis of multiple traits. This research proposes an integrative index for quantifying and evaluating PP. The multivariate plasticity index (MVPi) was calculated based on the Euclidian distance between scores of a canonical variate analysis. It was evaluated for leaf physiological traits in two cases using Brazilian Cerrado species and sugarcane varieties, grown under diverse environmental conditions. The MVPi was sensitive to plant behaviour from simple to complex genotype–environment interactions and was able to inform coarse and fine changes in PP. It was correlated to biomass allocation, showing agreement between plant organizational levels. The new method proved to be elucidative of plant metabolic changes, mainly by explaining PP as an integrated process and emergent property. We recommend the MVPi method as a tool for analysis of phenotypic plasticity in the context of a systemic evaluation of plant phenotypic traits.